The superwoman1‐cleistogamy2 mutant is a novel resource for gene containment in rice. Issue 1 (18th July 2016) - Lombardo, Fabien; Kuroki, Makoto; Yao, Shan‐Guo; Shimizu, Hiroyuki; Ikegaya, Tomohito; Kimizu, Mayumi; Ohmori, Shinnosuke; Akiyama, Takashi; Hayashi, Takami; Yamaguchi, Tomoya; Koike, Setsuo; Yatou, Osamu; et al.
Summary: Outcrossing between cultivated plants and their related wild species may result in the loss of favourable agricultural traits in the progeny or escape of transgenes in the environment. Outcrossing can be physically prevented by using cleistogamous (i.e. closed‐flower) plants. In rice, flower opening is dependent on the mechanical action of fleshy organs called lodicules, which are generally regarded as the grass petal equivalents. Lodicule identity and development are specified by the action of protein complexes involving the SPW1 and OsMADS2 transcription factors. In the superwoman1‐cleistogamy1 ( spw1‐cls1 ) mutant, SPW1 is impaired for heterodimerization with OsMADS2 and consequently spw1‐cls1 shows thin, ineffective lodicules. However, low temperatures help stabilise the mutated SPW1/OsMADS2 heterodimer and lodicule development is restored when spw1‐cls1 is grown in a cold environment, resulting in the loss of the cleistogamous phenotype. To identify a novel, temperature‐stable cleistogamous allele of SPW1, targeted and random mutations were introduced into the SPW1 sequence and their effects over SPW1/OsMADS2 dimer formation were assessed in yeast two‐hybrid experiments. In parallel, a novel cleistogamous allele of SPW 1 called spw1‐cls2 was isolated from a forward genetic screen. In spw1‐cls2, a mutation leading to a change of an amino acid involved in DNA binding by the transcription factor was identified. Fertility of spw1‐cls2 is somewhat decreased under low temperatures but unlike for spw1‐cls1, the cleistogamous phenotype is maintained, making the line a safer and valuable genetic resource for gene containment.